Higher Defense Organization in Nepal - Sharma, Suresh (Asian Journal of International Affairs, 2021)
An efficient Higher Defense Organization (HDO) is mandatory for any nation to match their national security objectives based on their geostrategic environment, challenges, and historical experiences. The components of HDO need efficiency, synergy, and decision-making ability to complement national interests. Nepal is experiencing diverse national security challenges of the millennia. In Nepal’s context, there is a requirement to revisit higher defense management components and enhance their capability so we guarantee their high-quality interface with elements of national power to effectively secure national interest. In the article, the HDO will be studied to identify our weaknesses to draw a framework of understanding.